Szkło w kulturze mieszkańców Poznania od późnego średniowiecza do pierwszej połowy XIX wieku - Twardosz, Bogumiła (Folia Praehistorica Posnaniensia, 2018)
The paper discusses luxury and ordinary glass vessels found during archaeological excavations conducted on several plots on the right and left bank of the Warta river in Poznań. A majority of glassware was discovered in the Szyperska Street, 21, where a big refuse dump was situated. The present paper is based on glass dated from the late Middle Ages to the first half of the 19th century. Glassware from Poznań was classified into 3 groups: table glass, glass storage containers and pharmacy glass. There were fragments of beakers, goblets, tankards, one mug, bowls, jugs, decanters, big bottles, small bottles, one jar, ampoules, phials and one pestle. Table glass fragments showed the greatest diversity of forms. All vessels were made in two basic techniques: socalled “free hand” technique or by blowing into the mould. Some of discovered glass was probably made in Germany, Bohemia, Pomerania, Silesia, Little Poland or Central Poland. Many of them were produced in Polish glassworks.